Character Transformation in Adaptation Life and Death Drives in Edward Ashton’s Mickey7 and Bong Joon Ho’s Mickey17 Movie Adaptation - Putri, Yulia Eka; Mesy Rino Nindia; Marsih, Linusia (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
The intention and purpose of creating adaptations are often discussed in the film adaptation and comparative study. By using adaptation theory from Desmond and Hawkes (2006) and the instinctive theory of life and death from Sigmund Freud, this research aims to analyse the different ideas between the novel “Mickey7” and the film “Mickey17”. The analysis includes finding the intrinsic elements of both data sources and by using Freud’s life and death instinct theory, psychoanalysing the two main characters. The result showed that “Mickey17” is an intermediate adaptation. The main characters in the novel, Mickey7 and Mickey8, represent the life instinct as they both want to live and show that they want to live by solving their problem together to not being eliminated. However, the main characters in the film, Mickey17 and Mickey18, represent life and death instincts, respectively. While Mickey17 has affection and sexual desire, Mickey18 is a Mickey who is more violent and antagonistic towards Mickey17 and the other characters around them.